A high-fidelity microfluidic platform reveals retrograde propagation as the main mechanism of α-Synuclein spread in human neurons - Rozan Vroman; Lorenzo de Lichtervelde; Karamjit Singh Dolt; Graham Robertson; Marco Kriek; Michela Barbato; Justyna Cholewa-Waclaw; Tilo Kunath; Patrick Downey; Michele Zagnoni (npj Parkinson's Disease)
Abstract α-Synuclein (αSyn) is a major component of Lewy bodies and Lewy neurites, which are a pathological hallmark of Parkinson’s disease (PD). Pathologically aggregated forms of αSyn can spread along neurites and induce the misfolding of normal αSyn. To elucidate how αSyn pathology propagates between brain areas, we developed a novel in vitro microfluidic platform to study the intracellular transport of preformed fibrils and the induction and spread of αSyn aggregates. Patient-derived midbrain dopaminergic (mDA) neurons were cultured in microfluidic devices designed to maintain unidirectional axonal connections between fluidically isolated mDA neuronal cultures for over 3 months. Using αSyn preformed fibrils to induce Lewy-like pathology, we found that anterograde spread of αSyn fibrils was slow and occurred at low levels, while retrograde spread was significantly more efficient. This is in line with observations in animal models and shows that the platform provides an innovative new tool for studying PD in vitro.